PEMBELAJARAN TANPA BATAS : PELAKSANAAN KURIKULUM MERDEKA YANG EFEKTIF DAN MOTIVASI BELAJAR TERHADAP PRESTASI - Nastiti, Cahya Rusetiana; Fr, Dewi Apriani; Nafiati, Dewi Amaliah (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to determine the influence of the independent curriculum, Learning Motivation, on the Learning Achievement of class X students at Ihsaniyah High School, Tegal City. This research is a type of quantitative research. Data collection methods used in this research are observation, questionnaires, documentation. Descriptive analysis techniques, simple linear regression analysis, multiple linear regression analysis, partial test and simultaneous test. The results of this research, namely the effectiveness of the independent curriculum, found that the implementation of this curriculum had a significant influence of 80.6% on student learning achievement. The effectiveness of the independent curriculum is proven to play an important role in increasing student academic achievement, showing that this curriculum effectively supports the achievement of better learning outcomes. Apart from that, learning motivation also contributes greatly to learning achievement, with an influence of 79%. This research underlines the importance of the effectiveness of learning motivation in improving student learning outcomes. When the combination of an independent curriculum and learning motivation is applied, the overall effectiveness reaches 84.6%, showing a strong synergy between the two in supporting student learning achievement. Thus, implementing an effective curriculum and developing high motivation is very important to achieve optimal learning achievement.